2012
DOI: 10.1111/j.1751-1097.2012.01088.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Response to Ultraviolet Radiation Exposure in Fish Embryos: Implications for Survival and Morphological Development

Abstract: UVR exposure is known to cause developmental defects in a variety of organisms including aquatic species but little is known about the underlying molecular mechanisms. In this work we used zebrafish (Danio rerio) embryos as a model system to characterize the UVR effects on fish species. Larval viability was measured for embryos exposed to several UVR spectral treatments by using a solar simulator lamp and an array of UV cutoff filters under controlled conditions in the laboratory. Survival rate and occurrence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…Embryos exposed to UV radiation followed a dosedependent relationship, with the number of dead embryos increasing as the UV radiation dose increased. A well-noticed effect of UV radiation on D. rerio embryos development was the occurrence of tail malformations, also observed in other studies [35,36]. This specific effect can be linked with the position of the embryos at the time of exposure to the UV radiation light.…”
Section: Rerio Single Exposuressupporting
confidence: 75%
See 3 more Smart Citations
“…Embryos exposed to UV radiation followed a dosedependent relationship, with the number of dead embryos increasing as the UV radiation dose increased. A well-noticed effect of UV radiation on D. rerio embryos development was the occurrence of tail malformations, also observed in other studies [35,36]. This specific effect can be linked with the position of the embryos at the time of exposure to the UV radiation light.…”
Section: Rerio Single Exposuressupporting
confidence: 75%
“…Nevertheless, the increased expression of the p53 gene can also lead to cell apoptosis, which in turn will cause the abnormal development of the embryo. Another finding of the study of Nuñez et al was the expression of the matricellular osteonectin protein increase under UV radiation exposure. This protein has a strong activity during embryogenesis, and it, too, has been linked to the formation of skin tumors in response to UV radiation .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Specifically, we showed that sparc is a modulator of lineage‐specific transcription factor gata 1 expression levels or activity. Furthermore, we demonstrated a UV exposure‐dependent increase in the expression of the matricellular protein osteonectin in zebrafish embryos (Torres‐Núñez et al, ). Therefore, because of its spatially and temporally regulated expression during development and its multifunctional role, sparc gene is expected to be tightly regulated.…”
Section: Introductionmentioning
confidence: 85%